2015
DOI: 10.1177/2167696815579828
|View full text |Cite
|
Sign up to set email alerts
|

Self-Doubt During Emerging Adulthood

Abstract: Emerging adulthood (EA) is a critical time for identity exploration and making decisions regarding the future. Although most thrive, some emerging adults struggle with the prominent developmental features of this time. Little is known about factors that may positively influence development during EA. This study examined the mediating impact of mindfulness on the relationship between normative emerging adult processes (identity exploration, experimentation/possibilities, negativity/instability, self-focus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Our findings are consistent with previous research that has examined the relationship between health and EA (Baggio et al, 2017; Barlett et al, 2020; Kohútová et al, 2021; Luyckx et al, 2011; Nelson & Barry, 2005; Ozer & Schwartz, 2020; Peer & McAuslan, 2016, 2016, 2016; Peñaflor et al, 2019; Yang et al, 2020). Specifically, our results suggest that individuals who perceive their health to be worse tend to have lower levels of EA: they are less likely to view their life as an opportunity for identity exploration, self-focus, and experimentation/possibilities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous research that has examined the relationship between health and EA (Baggio et al, 2017; Barlett et al, 2020; Kohútová et al, 2021; Luyckx et al, 2011; Nelson & Barry, 2005; Ozer & Schwartz, 2020; Peer & McAuslan, 2016, 2016, 2016; Peñaflor et al, 2019; Yang et al, 2020). Specifically, our results suggest that individuals who perceive their health to be worse tend to have lower levels of EA: they are less likely to view their life as an opportunity for identity exploration, self-focus, and experimentation/possibilities.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding gender, the results show that women are more inclined to identify as emerging adults than men, supporting findings from Leontopoulou et al (2016) and Peer and McAuslan (2016). However, these findings contradict other studies, in which no relationship between IDEA and gender was observed (Arnett, 2003; Ismyrlis, 2021; Mattys et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…One coping mechanism that has been proposed for emerging adults is mindfulness. Peer and McAuslan (2016) found that trait mindfulness mediated the association between challenges characteristic to emerging adulthood and self-doubt, highlighting the usefulness of mindfulness for emerging adults. Research has recently started investigating the relationship between perfectionism and mindfulness in students.…”
Section: Introductionmentioning
confidence: 88%
“…They found that emerging adults who were identity achieved were less likely to have negative views of the past and fatalistic views of the future, along with greater acceptance of the present and increased mindfulness, whereas those who were identity diffused were more likely to have negative views of the past and lacked concern for the future. Additional research indicates that mindfulness mediates the relationships between developmental challenges of emerging adulthood and self-doubt regarding identity commitments (Peer & McAuslan, 2016). Within this context, mindfulness can be seen as a psychological resource designed to foster awareness and acceptance of identity-and career-related cognitions and emotions, thus reducing distress related to career indecision and worry about work-related uncertainties.…”
Section: Dmmentioning
confidence: 99%